Combination of Selenium and Methyl Jasmonate Controls Postharvest Tomato Gray Mold by Damaging the Membrane System - Xiang Yuan; Changyin Li; Jiatao Xie; Keyi Li; Siqi Chen; Linxi Yuan; Chengxiao Hu; Xu Wang; Xiaohu Zhao (Horticulturae, 2022)
Tomato, which is regarded as an important worldwide crop, is susceptible to gray mold caused by Botrytis cinerea. Selenium and methyl jasmonate can act as antifungal agents against pathogenic infections. To clarify the effect of selenium and methyl jasmonate on the fungal pathogen, the spore germination and mycelial growth of B. cinerea were investigated in vitro using the growth rate method. Additionally, the electrical conductivity, soluble protein content, malondialdehyde content and oxalic acid secretion of B. cinerea mycelium were also determined to further explore the antifungal mechanism of selenium and methyl jasmonate. The results showed that selenium application significantly increased cell membrane permeability and malondialdehyde content, and methyl jasmonate treatment decreased the soluble protein content in mycelium of B. cinerea. Furthermore, supplementation of the medium with both selenium and methyl jasmonate effectively inhibited spore germination and colony growth of B. cinerea by compromising membrane integrity, and significantly reduced soluble protein content and the oxalic acid secretion of hypha. The resulting incidence of postharvest tomato gray mold with the combination of selenium and methyl jasmonate was 34.7%, which was approximately half of that of the control. To sum up, the combined use of selenium and methyl jasmonate inhibited the normal physiological activity and pathogenicity of B. cinerea, which suggests that selenium and methyl jasmonate have the potential for controlling gray mold disease caused by B. cinerea in postharvest fruits and vegetables. These findings may offer a promising and eco-friendly strategy to control gray mold disease in postharvest fruits and vegetables.